Correction: Media representations of China's inclusive education: A corpus-assisted critical discourse analysis. - Yating Yu; Gaoqiang Lu; Kuen Fung Sin; Zhiying Yu (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0300123.].